Relation of Knowledge About Breast Cancer with Breast Self-Examination (BSE) Behavior Implementation on Childbearing Age Women in Bandung - Chris Sriyanti (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Breast cancer is a serious threat for women all over the world including Indonesia. Self Breast-Examination (BSE) is one of important early detection efforts in reducing morbidity and mortality due to breast cancer. The implementation of BSE as a behavior is influenced by many factors, including knowledge. This study aims was to analyze the relation of knowledge about breast cancer with the behavior of BSE implementation on childbearing age women at Bandung, West Java. Cross-sectional design was used with 420 respondents. Women over the age of 20 were randomly selected to participate in this study. Questionnaire was used as data collection instrument. Data was analyzed by using Chi-Square with statistical significance level at p <0.05. The results showed that 56.2% of respondents had good knowledge about breast cancer and 43.8% were still at low level, while the implementation of BSE was also still low at 39% (IK 95%: 34, 5% -43.8%). There was significant relation between knowledge about breast cancer and the behavior of BSE implementation on childbearing age women in Bandung (p <0.001).